Determination of Riboflavin and Cyanocobalamine Spectrophotometricaly via Area Under Curve Method - Mohammed Qasim Al-Samarrai; Khlaf F Al-Samarrai (Tikrit Journal of Pure Science, 2023)
A simple, sensitive, accurate and economical spectrophotometric method for determination of Riboflavin (RIBO) and Cyanocobalamin (CCA) in pure and pharmaceutical forms was developed .The method based on the area under curve (AUC) in the region between 400-526 nm for RIBO and 538-562nm for CCA. The method obey Beers law in the concentration range between 10- 90 µg.ml-1 of  RIBO and 6- 96 µg.ml-1 of CCA. The Rec% range was between 97.6542-103.5198 % and RSD% 0.5871-0.7542 % , LOD 0.2168 µg.ml-1,  LOQ 0.8560 µg.ml-1 of  RIBO.   The Rec% range was between 99.7835-102.3990 % and RSD%  0.4811-0.8238 % and LOD 0.1381 µg.ml-1,  LOQ 0.4606 µg.ml-1 of  CCA .